(untitled) (Bangladesh Journal of Dental Research & Education, 2013)
Obstructive Sleep Apnea Syndrome is a life threatening sleep disorder which can occur as consequences of some body conditions. On the other hand it causes many systemic diseases as well as accidental injury. There is no prevalence study in Bangladesh but its prevalence is higher in western countries. Proper diagnosis and treatment is essential. Surgical treatment of this disease gives permanent cure. Maxillofacial surgeon has a vital role in treating this disease. ENT surgeon as well as prosthodontist can help the OSAS patient as well. DOI: http://doi.dx.org/10.3329/bjdre.v2i2.16247 Bangladesh Journal of Dental Research & Education Vol.2(2) 2012: 62-64